PENGARUH PELATIHAN DAN KOMPETENSI PENGELOLA WISATA TERHADAP KUALITAS PELAYANAN PADA OBJEK WISATA PANTAI TANJUNG LAYAR SAWARNA KABUPATEN LEBAK BANTEN - Pipin Suryanisari; Irma Hermawati; Euis Ajizah (The Asia Pacific Journal Of Management Studies, 2024)
The purpose of this study was to determine and analyze the effect of training andcompetence of tourism managers on service quality at Tanjung Layar Sawarna beach tourist attraction, Lebak Banten Regency. The method used in this research is Quantitative Descriptive research method. The sampling technique used was random, the sample in this study consisted of 36 managers at the Tanjung Layar Sawarna beach tourist attraction. And data collection techniques carried out using the distribution of questionnaires that meet the criteria in this study. Testing of this research was carried out using data instrument tests, classical assumption tests, then analyzed by correlation tests and multiple linear regression tests using the IBM SPSS (Statistical Program For Social Science) v.20 program. The results showed that there was a partial influence between Training on Service Quality, the results of the t test on Training obtained a significant value of 0.02 <0.05 and a tcount value of 3.319> t table 2.035 so it can be concluded that Ho is rejected and Ha is accepted, meaning that there is an influence of X1 on Y and significant on Y. The results showed that there was a partial influence between Competence on Service Quality, the results of the t test on Competence obtained 0.041 <0.05 and a tcount value of 2.128> 0.041 so it can be concluded that Ho is rejected and Ha is accepted, meaning that X2 has an influence and is significant on Y. The results of the F test menu are as follows.